SIGN LANGUAGE ACQUISITION AS L2 FOR HEARING STUDENTS - Maria Martins Viana Rienda, Kamila; Soroldoni de Souza, Valdenice; do Espirito Santo Ornelas, Camila (Revista Gênero e Interdisciplinaridade, 2025)
This paper presents a brief reflection on the beginning of deaf education in Brazil and the emergence of laws that support the education of deaf people, seeking theoretical references and relating practical experience, considering the coexistence and interaction between deaf and hearing people through the observation of contact in the school routine during the implementation of the Libras Project and analysis of a questionnaire developed with the 7th grade class, group B, of the “C.E.E.F.M.T.I. Aristeu Aguiar” located in the city of Alegre/ES. Thus, with the aim of presenting the importance of teaching Libras to hearing students, in addition to stimulating and awakening interest in the acquisition of sign language, we justify the chosen theme since in order to have the real inclusion of deaf people in the school context, it is necessary to disseminate sign language among hearing students, with the school being the ideal place for this interaction to occur and exposes the need for methodologies that aim to awaken the student’s interest in the acquisition of Libras as L2 for hearing students.